NITROGEN DYNAMICS OF A BOREAL BLACK SPRUCE WILDFIRE CHRONOSEQUENCE - Bond-Lamberty B.; Gower S.T.; Wang C.; Cyr P.; Veldhuis H. (My University, 2006)
This study examined the nitrogen (N) dynamics of a black spruce (Picea mariana (Mill.) BSP)-dominated chronosequence in Manitoba, Canada. The seven sites studied each contained separate well- and poorly drained stands, originated from stand-killing wildfires, and were between 3 and 151 years old. Our goals were to (i) measure total N concentration ([N]) of all biomass components and major soil horizons; (ii) compare N content and select vegetation N cycle processes among the stands; and (iii) examine relationships between ecosystem C and N cycling for these stands. Vegetation [N] varied significantly by tissue type, species, soil drainage, and stand age; woody debris [N] increased with decay state and decreased with debris size. Soil [N] declined with horizon depth but did not vary with stand age. Total (live + dead) biomass N content ranged from 18.4 to 99.7 g N m-2 in the well-drained stands and 37.8-154.6 g N m-2 in the poorly drained stands. Mean soil N content (380.6 g N m-2) was unaffected by stand age. Annual vegetation N requirement (5.9 and 8.4 g N m-2 yr-1 in the middle-aged well- and poorly drained stands, respectively) was dominated by trees and fine roots in the well-drained stands, and bryophytes in the poorly drained stands. Fraction N retranslocated was significantly higher in deciduous than evergreen tree species, and in older than younger stands. Nitrogen use efficiency (NUE) was significantly lower in bryophytes than in trees, and in deciduous than in evergreen trees. Tree NUE increased with stand age, but overall stand NUE was roughly constant (~150 g g-1 N) across the entire chronosequence. © 2006 Springer Science+Business Media, Inc.
Keywords: BIOGEOCHEMICAL CYCLING; BOREAL FOREST; PICEA MARIANA; PINUS BANKSIANA; POPULUS TREMULOIDES; SPHAGNUM